The Analysis of Mythological Symbols in Shahnameh - موسی پرنیان; شهرزاد بهمنی (متن شناسی ادب فارسی, 2012)
Recognizing symbols of Shahnameh requires an understanding of the context and condition of creation and emergence of symbol, myth and epic. Symbol has a relationship with consciousness and unconsciousness of man and constitutes the language of mythologies, legends, and epics. Thus the language of mythological and epic works is symbolic. The main theme in Iranian mythologies is the dual nature of creation, and during the passage from myth to epic the conflict between the two forces of good and evil appear in various aspects of existence. Some characters that represent symbolic and coded concepts more than other elements can be considered as symbols of the evolution of gods to kings and against them there are devilish kings as symbols of drought (Apush). The other symbolic elements analyzed in this study are: epic-romance stories, imaginary creatures, symbolic dreams of kings and heroes, symbolic numbers, symbolic patterns of flags, the symbolism of water, fire and charisma The findings of the study illustrate that people, more than other elements, are the constitutive elements of mythological symbols, and the tension between these human elements depicts the mutual conflict between good and evil in Ferdowsiâs Shahnameh. Like other elements, symbolic characters (especially kings) are of symbolic value and constitute a part of constructing elements of mythological symbols in Shahname. Moreover their reputation is dependent on the extent of their benefit from âGod charismaâ as the most pivotal element of their personality. Kings like Afrasiab and Zahak, due to lack of it, are the most disreputable kings. On the other hand, Fereidoon and Kaikhosro are on the top of the most reputable kings because of continuous benefit from that. This study has been conducted on the basis of library resources and has applied a descriptive-analytic method.